2016
DOI: 10.1007/s00122-015-2655-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection in a commercial winter wheat population

Abstract: Genomic selection models can be trained using historical data and filtering genotypes based on phenotyping intensity and reliability criterion are able to increase the prediction ability. We implemented genomic selection based on a large commercial population incorporating 2325 European winter wheat lines. Our objectives were (1) to study whether modeling epistasis besides additive genetic effects results in enhancement on prediction ability of genomic selection, (2) to assess prediction ability when training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 57 publications
11
114
3
Order By: Relevance
“…The recently developed iSelect 9K and 90K arrays (Cavanagh et al, 2013; Wang et al, 2014) designed to characterize genetic variation in hexaploid wheat populations have extensive applications in QTL mapping (Wu et al, 2015b), genome-wide association studies (GWAS) (Gao et al, 2016), genomic selection (He et al, 2016), and establishment of heterotic groups (Zhao et al, 2015). In the present study, we constructed a dense genetic linkage map for the Y8679/J411 RIL population, using 10,816 polymorphic SNP markers from an iSelect 90K array and 174 polymorphic SSR markers.…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed iSelect 9K and 90K arrays (Cavanagh et al, 2013; Wang et al, 2014) designed to characterize genetic variation in hexaploid wheat populations have extensive applications in QTL mapping (Wu et al, 2015b), genome-wide association studies (GWAS) (Gao et al, 2016), genomic selection (He et al, 2016), and establishment of heterotic groups (Zhao et al, 2015). In the present study, we constructed a dense genetic linkage map for the Y8679/J411 RIL population, using 10,816 polymorphic SNP markers from an iSelect 90K array and 174 polymorphic SSR markers.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic selection can be a valuable tool to accelerate genetic gains in plant breeding programs, and has been described as a valuable tool in several plant species (for example wheat and maize [12,34]). Genomic selection has only just started in barley breeding [35].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic selection using genome-wide dense marker maps has been suggested as a more efficient alternative to conventional selection methods (Meuwissen et al 2001) and several studies have shown its great potential in line breeding to enhance the selection for major agronomic traits like yield both in legumes (JarquĂ­n et al 2014; Burstin et al 2015; Tayeh et al 2015) and small grain cereals (Asoro et al 2011; Sallam et al 2015; Spindel et al 2015; He et al 2016; Michel et al 2016). Additionally, genomic selection could support the accumulation of many small effect alleles to provide higher and more durable quantitative disease resistance (Lorenz et al 2012; Ornella et al 2012; Daetwyler et al 2014; Arruda et al 2015; Rutkoski et al 2015b), which could be subsequently combined with labor-intensive and costly to assess quality traits (Heffner et al 2011b; Schmidt et al 2015).…”
Section: Introductionmentioning
confidence: 99%